2011
DOI: 10.2319/090510-520.1
|View full text |Cite
|
Sign up to set email alerts
|

Do fluoride and casein phosphopeptide–amorphous calcium phosphate affect shear bond strength of orthodontic brackets bonded to a demineralized enamel surface?

Abstract: Objective: To compare the effects of fluoride and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) containing topical agents on shear bond strength (SBS) and fracture mode of orthodontic brackets bonded to demineralized enamel. Materials and Methods: Eighty freshly extracted human premolar teeth were randomly divided into four equal groups. The first group was the control, and no pretreatment was performed on this group. In the remaining three groups, demineralization process was performed and teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 44 publications
(42 reference statements)
9
54
0
Order By: Relevance
“…Recently, we compared fluoride and CPP-ACP pretreatment on the shear bond strength (SBS) of brackets bonded to demineralized enamel. 24 CPP-ACP pretreatment resulted in SBS values that were similar to those of the control group. In the present study, the aim is to evaluate the effects of microabrasion, CPP-ACP application, and combinations of these procedures on the SBS of orthodontic brackets bonded to a demineralized enamel surface.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…Recently, we compared fluoride and CPP-ACP pretreatment on the shear bond strength (SBS) of brackets bonded to demineralized enamel. 24 CPP-ACP pretreatment resulted in SBS values that were similar to those of the control group. In the present study, the aim is to evaluate the effects of microabrasion, CPP-ACP application, and combinations of these procedures on the SBS of orthodontic brackets bonded to a demineralized enamel surface.…”
Section: Introductionmentioning
confidence: 58%
“…Clinicians may help these patients and complete their treatment with several enamel pretreatment procedures. In a recent study, 24 we evaluated the effects of CPP-ACP and fluoride applied to demineralized enamel and compared them with a control group. In that study, higher SBS was found in the control group compared to pretreated groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although enamel detachment was seen in the groups, SEPs provide us with clinically acceptable SBS values except for the demineralization group. Demineralization of teeth decreases the quality of bonding as stated by Uysal et al 12 and Ekizer et al 14 The surface roughness of teeth and restoration correlates directly with the retention of plaque because bacteria adhere more readily to rough surfaces. The mean critical value of surface roughness for bacterial colonization has been defined as 0.2 mm.…”
Section: Discussionmentioning
confidence: 90%
“…In the studies mentioned above, natural enamel surfaces were used. On the other hand, Uysal et al 12 compared the effects of fluoride and CPP-ACP and Baysal and Uysal 13 compared the effects of microabrasion and CPP-ACP on the SBS of orthodontic brackets bonded to demineralized enamel and found no significant differences between the control and CPP-ACP groups. In both studies, pretreatment of artificially demineralized surfaces with remineralization procedures appeared to restore decreased SBS values of orthodontic brackets, which is in accordance with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…(Siverstone, 1982;Artun& Thylstrup, 1986;Øgaard & Rolla, 1988) To prevent WSL formation, topical fluoride containing mouth rinse and tooth pastes are recommended for patients and orthodontists may take precaution such as the use of fluoride-releasing adhesive materials and elastics. Daily routine use of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) containing tooth pastes (Wiltshire, 1999;Fraizer & Southard, 1996;Lefeuvre & Amjaad, 2005;Uysal & Baysal, 2011) or fluoride containing mouth rinses (Gorelick & Geiger, 1982;Jordan, 1998) have been reported to significantly inhibit the formation of WSLs. However during all of these applications, the effective use has vital importance.…”
Section: Problem Encountered After Orthodontic Treatmentmentioning
confidence: 99%